2012
DOI: 10.1589/jpts.24.589
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Electromagnetic Field Elicits Muscle Recovery via Increase of HSP 70 Expression after Crush Injury of Rat Skeletal Muscle

Abstract: Abstract.[Purpose] The present study investigated the effects of electromagnetic field applied at different time points on muscle recovery process through observation of the expression of HSP 70 protein and histological changes in a rat muscle crush injury model. [Subjects and Methods] Fifty-four male Sprague-Dawley rats were subjected to crush injury of the left extensor digitorum longus muscle. The animals were randomly assigned to the control (CON), pulsed electromagnetic fields (PEMF), delayed PEMF (DPEMF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Previous studies have shown pulsed electromagnetic fields (PEMF) to have benefits in muscle disease recovery, e.g. inducing muscle regeneration in crush injuries [Cheon et al, 2012], promoting tendon‐bone healing [Tucker et al, 2017], and increasing the rate of nerve regeneration [Mert et al, 2006; Beck‐Broichsitter et al, 2014]. Although the contribution of PEMF to recovery from musculoskeletal disorders has been shown, its effect on immobilization‐induced atrophy formation is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown pulsed electromagnetic fields (PEMF) to have benefits in muscle disease recovery, e.g. inducing muscle regeneration in crush injuries [Cheon et al, 2012], promoting tendon‐bone healing [Tucker et al, 2017], and increasing the rate of nerve regeneration [Mert et al, 2006; Beck‐Broichsitter et al, 2014]. Although the contribution of PEMF to recovery from musculoskeletal disorders has been shown, its effect on immobilization‐induced atrophy formation is unknown.…”
Section: Introductionmentioning
confidence: 99%